2013
DOI: 10.3390/atmos4040337
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Size Distribution of Fungi Aerosol over Oceans along a Cruise Path during the Fourth Chinese Arctic Research Expedition

Abstract: Bioaerosol can act as nuclei and thus may play an important role in climate change. During the Fourth Chinese National Arctic Research Expedition (CHINARE 2010) from July to September 2010, the concentrations and size distributions of airborne fungi, which are thought to be one of important bioaerosols, in the marine boundary layer were investigated. The concentrations of airborne fungi varied considerably with a range of 0 to 320.4 CFU/m 3 . The fungal concentrations in the marine boundary layer were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this study, B. cinerea aerosols were produced by a six-jet Collison nebulizer in exposure chambers to avoid other transmission routes, and the results proved that B. cinerea aerosols instead of other transmission factors cause grape gray mold. Fungi in bioaerosols are generally derived from soil, water, plants, animals, and so on [ 46 , 47 ]. Temperature, humidity, wind, and sea ice are important meteorological conditions that influence the concentrations and sizes of airborne fungi [ 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, B. cinerea aerosols were produced by a six-jet Collison nebulizer in exposure chambers to avoid other transmission routes, and the results proved that B. cinerea aerosols instead of other transmission factors cause grape gray mold. Fungi in bioaerosols are generally derived from soil, water, plants, animals, and so on [ 46 , 47 ]. Temperature, humidity, wind, and sea ice are important meteorological conditions that influence the concentrations and sizes of airborne fungi [ 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The size of bioaerosols is a main factor that impacts their ability to reach plant tissues through natural openings and successfully infect host plants [ 21 ]. Previous studies showed that the size distributions of airborne fungi ranged from 0.65 µm to larger than 7 µm [ 39 , 47 ]. In our study, approximately 38% of B. cinerea aerosols were distributed in the 1.1–2.1 μm range, and particle sizes of 4.7–7.0 µm were the least frequent (accounting for 7.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Managing these risks necessitates conducting checks at different stages of the process, such as deploying sealed bottles/tubes/bags/buckets containing sterile seawater on‐site to detect any potential contamination. Aerosol samples at sea can be taken at the time of seawater sampling, using common air samplers such as quartz fiber or glass fiber filter‐based devices for culture‐independent analysis (Fröhlich‐Nowoisky et al., 2012), and six‐stage Andersen impactor (Yu et al., 2013) or Burkard sampler (Mescioglu et al., 2021) for culture‐based examination. This allows for the assessment of culturable fungal diversity in the sampled air, providing a basis for comparison with the fungal diversity in the seawater at the same time of sampling.…”
Section: Methods For Studying Planktonic Marine Fungimentioning
confidence: 99%
“…Managing these risks necessitates conducting checks at different stages of the process, such as deploying sealed bottles/tubes/bags/buckets containing sterile seawater onsite to detect any potential contamination. Aerosol samples at sea can be taken at the time of seawater sampling, using common air samplers such as quartz fiber or glass fiber filter-based devices for culture-independent analysis (Fröhlich-Nowoisky et al, 2012), and six-stage Andersen impactor (Yu et al, 2013) or Burkard sampler (Mescioglu et al, 2021) for culturebased examination. This allows for the assessment of culturable fungal diversity in the sampled air, providing a basis for comparison with the fungal diversity in the seawater at the same time of sampling.…”
Section: Cultivation-based Methodsmentioning
confidence: 99%